Maria Hablevych and the Concept of Truth in ’Hamlet’ - Sverediuk, Anna (Vertimo studijos, 2023)
The paper is focused on the interpretation of the notion of Truth in Ukrainian translations of Hamlet through the lenses of the contemporary Ukrainian Shakespeare Studies scholar Maria Hablevych (1950). In particular, it deals with the reproduction of Truth based on the notion of agent’s professional habitus, which is regarded as a heterogeneus entity with several sub-habiti. The paper is an attempt to prove that multifaceted agency as the result of complex habitus, reflected in the agent’s hexis, or style, facilitates better understanding and re-interpretation of the issues raised in Shakespeare’s tragedy. The research touches upon the Ukrainian translator-agents, with some of them being committed to more than one agency, to trace the influence of the existing restrictive norms on their habiti and the respective interpretation of Truth in Shakespeare’s tragedy.